Obstacles in the access to public health services by transvestites and transgender persons: an integrative review - Liniker Scolfild Rodrigues da Silva; Lusanira Maria da Fonseca de Santa Cruz; Luiz Valério Soares da Cunha Junior; Hélio Monteiro da Silva Filho; Danilo Martins Roque Pereira; Ednaldo Cavalcante de Araújo (Rev Rene)
Objective: to describe obstacles to the access to health services of the transvestite and transgender population. Methods: integrative review, conducted from July to August 2022, in the following databases: LILACS, MEDLINE, Web of Science and SCOPUS. Results: 472 primary studies were found; however, at the end of the analysis process, 14 productions were included in the study. Obstacles to access to health were observed, such as the invisibility of health specificities, the lack of information and preparation of professionals, the susceptibility, which appears in the juvenile stage, and the resistance to care for sexually transmitted infections, highlighting the need to invest in the production of policies that affirm the right to health for this segment of the population. Conclusion: there was a lack of studies on the access of transvestites and transgenders to health services. These difficulties are associated with conservatism, heteronormativity, lack of implementation and regulation of public policies for them. Contributions to practice: this article presents information about access to health care for the transvestite and transgender population, facilitating the view of the specific needs of this population.